An Efficient and Highly Secure Technique to Encrypt and Decrypt Color Images - Al-Dwairi, M. O.; Hendi, A. Y.; AlQadi, Z. A. (Engineering, Technology & Applied Science Research, 2019)
Digital color images are considered as the most widely used data. They are exchanged frequently on the internet and via email, so an efficient and highly secure method of color image encryption and decryption is needed. Different methods of encryption-decryption are used, but most of them suffer from low efficiency or low-security level or both. In this paper, an efficient and highly secure method of encryption-decryption will be proposed, tested, and implemented. The efficiency parameters will be calculated and compared with other methods’ parameters to prove the efficiency of the proposed method.